2021
DOI: 10.1021/acsanm.1c00102
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Rhamnolipid Molybdenum Disulfide Nanosheets for Oil Recovery

Abstract: Much attention has been directed toward amphiphilic nanosheets in diverse applications owing to their remarkable properties. In this work, the rhamnolipid-molybdenum disulfide nanosheets, environmentally friendly biological-amphiphilic-nanosheets (BANs), are prepared through the one-step simple hydrothermal method. The ultralow concentration of BANs (0.005 wt %), as a solid emulsifier, can emulsify crude oil and stabilize the size of emulsions (oil in water) within 1.2 μm. The adsorption of BANs to the oil−wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The assembly of nanoparticles at the oil–water interface has received widespread attention and has been extensively studied by numerous investigators. These studies include but are not limited to food processing and production, drug encapsulation, , environmental remediation, and enhanced oil recovery. The interest stems from the fact that particle-laden interfaces offer a route to controlled interfacial properties, including the ultimate stability of an emulsion. Oil droplets surrounded by particles result in improved viscoelastic properties of the interface. Hence, emulsion breakup, coalescence, or coarsening can be circumvented or slowed. , …”
Section: Introductionmentioning
confidence: 99%
“…The assembly of nanoparticles at the oil–water interface has received widespread attention and has been extensively studied by numerous investigators. These studies include but are not limited to food processing and production, drug encapsulation, , environmental remediation, and enhanced oil recovery. The interest stems from the fact that particle-laden interfaces offer a route to controlled interfacial properties, including the ultimate stability of an emulsion. Oil droplets surrounded by particles result in improved viscoelastic properties of the interface. Hence, emulsion breakup, coalescence, or coarsening can be circumvented or slowed. , …”
Section: Introductionmentioning
confidence: 99%
“…Different masses of ODA-MoS 2 were weighed and dispersed in 100 mL of simulated formation water, and then the different concentrations of ODA-MoS 2 nanofluids can be obtained by an ultrasonic cleaning instrument (EYG-3010) for 5 min. It has been demonstrated that the ODA-MoS 2 nanofluid has good stability by high-temperature and salt-resistance experiments, and the specific experimental results can be found in ref .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The volume of discharged water from the outlet end is the initial oil content of the core ( V oi ), and the volume of irreducible water is expressed as V wi = V – V oi . The core that was saturated with crude oil was aged at 45 °C for 14 days …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, structural disjoining pressure could be formed by AMH nanosheets at the confinement of the three-phase contact region, which contributes to the dynamic spreading of nanosheets on the solid surface and detachment of oil from the surface. Qu et al 26 found that the spreading rate of the three-phase contact line was in the range from 9.7 × 10 −6 to 2.8 × 10 −5 cm/s under the effect of amphiphilic nanosheets at a ultralow concentration (50 mg/L). Considering that the changes in the contact angle under the effect of MH and NH 2 -MH were insignificant, the adsorption of AMH on the solid surface may be the dominant reason for its superior wettability alteration ability.…”
Section: Characterizations Of Nanosheetsmentioning
confidence: 99%